High and dry: post‐fire tree seedling establishment in subalpine forests decreases with post‐fire drought and large stand‐replacing burn patches. Issue 6 (16th March 2016) - Harvey, Brian J.; Donato, Daniel C.; Turner, Monica G.
Abstract: Aim Climate warming and increased wildfire activity are hypothesized to catalyse biogeographical shifts, reducing the resilience of fire‐prone forests world‐wide. Two key mechanisms underpinning hypotheses are: (1) reduced seed availability in large stand‐replacing burn patches, and (2) reduced seedling establishment/survival after post‐fire drought. We tested for regional evidence consistent with these mechanisms in an extensive fire‐prone forest biome by assessing post‐fire tree seedling establishment, a key indicator of forest resilience. Location Subalpine forests, US Rocky Mountains. Methods We analysed post‐fire tree seedling establishment from 184 field plots where stand‐replacing forest fires were followed by varying post‐fire climate conditions. Generalized linear mixed models tested how establishment rates varied with post‐fire drought severity and distance to seed source (among other relevant factors) for tree species with contrasting post‐fire regeneration adaptations. Results Total post‐fire tree seedling establishment (all species combined) declined sharply with greater post‐fire drought severity and with greater distance to seed sources (i.e. the interior of burn patches). Effects varied among key species groups. For conifers that dominate present‐day subalpine forests ( Picea engelmannii, Abies lasiocarpa ), post‐fire seedling establishment declined sharply with both factors. One exception was serotinous Pinus contorta, which did not vary with either factor. For montane species expected to move upslope under future climate change ( Larix occidentalis, Pseudotsuga menziesii, Populus tremuloides ) and upper treeline species ( Pinus albicaulis ), establishment was unrelated to either factor. Greater post‐fire tree seedling establishment on cooler/wetter aspects suggested local topographic refugia during post‐fire droughts. Main conclusions If future drought and wildfire patterns manifest as expected, post‐fire tree seedling establishment of species that currently characterize subalpine forests could be substantially reduced. Compensatory increases from lower montane and upper treeline species may partially offset these reductions, but our data suggest important near‐ to mid‐term shifts in the composition and structure of high‐elevation forests under continued climate warming and increased wildfire activity.